Characterization of the LhcSR Gene Under Light and Temperature Stress in the Green Alga Ulva linza - Dong, Meitao; Zhang, Xiaowen; Zhuang, Zhimeng; Zou, Jian; Ye, Naihao; Xu, Dong; Mou, Shanli; Liang, Chengwei; Wang, Wenqi (Plant molecular biology reporter, 2012)
As a green-tide-forming macroalga, Ulva linza is distributed worldwide and therefore subject to various environmental stresses. The LHCSR (also known as LI818 in green alga and LHCX in diatoms) protein is a stress-related member of the LHC family that plays an important role in photo-protective mechanism, which has been only found in algae. In this study, we cloned full-length cDNA sequence encoding the Lhc SR gene from U. linza and analyzed its expression in response to different temperature and illumination gradients. The results showed that high light (HL) could enhance expression of Lhc SR and that the expression level peaked at 3 h under HL. Similarly, the expression of Lhc SR could also be induced by low temperature (LT). However, the expression patterns of Lhc SR were quite different in response to LT and HL treatment. Specifically, the maximum gene expression under LT was much higher (11.8-fold) than under HL (5.4-fold) when compared to the expression under normal conditions. The upregulated expression of Lhc SR lasted for 12 h under LT, but 3 h under HL. These data suggest that the Lhc SR gene is involved in photoprotection in U. linza , and the results suggest a stronger link to LT. In addition, the discrepancy in expression under HL and LT was consistent with the ecological features of this alga, which only thrives during the cold season (featured as LT and low light).